2023
DOI: 10.1007/s00018-022-04673-9
|View full text |Cite
|
Sign up to set email alerts
|

Brain histone beta-hydroxybutyrylation couples metabolism with gene expression

Abstract: Little is known about the impact of metabolic stimuli on brain tissue at a molecular level. The ketone body beta-hydroxybutyrate (BHB) can be a signaling molecule regulating gene transcription. Thus, we assessed lysine beta-hydroxybutyrylation (K-bhb) levels in proteins extracted from the cerebral cortex of mice undergoing a ketogenic metabolic challenge (48 hrs fasting). We found that fasting enhanced K-bhb in a variety of proteins including histone H3. ChIP-seq experiments showed that K9 betahydroxybutyrylat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…As seen in Table 2, despite the diverse functions of the Kbhb proteins, there is an enrichment of β-hydroxybutyrylated proteins related to the regulation of the genome and its expression, including chromatin structure, transcript processing and DNA repair (Xie et al, 2016;Huang et al, 2021;Cornuti et al, 2023) Likewise, Kbhb is enriched in proteins related to fatty acid, amino acid and pyruvate metabolism, the regulation of tricarboxylic acid cycle, oxidative phosphorylation, and detoxification pathways, among others (Koronowski et al, 2021;Hou et al, 2022;Luo et al, 2023). Interestingly, 2-day starvation induced an increase in Kbhb in the cerebral cortex, mainly in proteins involved in transcription regulation, transcription dependent on RNA pol II, and morphogenesis (Cornuti et al, 2023). Surprisingly, while approximately 53% of β-hydroxybutyrylated proteins contain only one Kbhb site, others harbor multiple or even more than ten Kbhb sites, as demonstrated in HEK293T cells treated with 10 mM BHB (Huang et al, 2021).…”
Section: Lysine β-Hydroxybutyrylation (Kbhb)mentioning
confidence: 99%
See 2 more Smart Citations
“…As seen in Table 2, despite the diverse functions of the Kbhb proteins, there is an enrichment of β-hydroxybutyrylated proteins related to the regulation of the genome and its expression, including chromatin structure, transcript processing and DNA repair (Xie et al, 2016;Huang et al, 2021;Cornuti et al, 2023) Likewise, Kbhb is enriched in proteins related to fatty acid, amino acid and pyruvate metabolism, the regulation of tricarboxylic acid cycle, oxidative phosphorylation, and detoxification pathways, among others (Koronowski et al, 2021;Hou et al, 2022;Luo et al, 2023). Interestingly, 2-day starvation induced an increase in Kbhb in the cerebral cortex, mainly in proteins involved in transcription regulation, transcription dependent on RNA pol II, and morphogenesis (Cornuti et al, 2023). Surprisingly, while approximately 53% of β-hydroxybutyrylated proteins contain only one Kbhb site, others harbor multiple or even more than ten Kbhb sites, as demonstrated in HEK293T cells treated with 10 mM BHB (Huang et al, 2021).…”
Section: Lysine β-Hydroxybutyrylation (Kbhb)mentioning
confidence: 99%
“…The rise of the physiological levels of ketone bodies whether induced by KD, starvation or the administration of BHB or its derivatives, has an impact in genome regulation and therefore in the protein content ( Xie et al, 2016 ; Cornuti et al, 2023 ).…”
Section: Ketone Bodies Induce Changes In the Proteome Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein beta-hydroxybutyrylation plays important roles in various cellular processes [ 154 , 155 ]. Xie et al showed that BHB induces lysine beta-hydroxybutyrylation (Kbhb) on histones and upregulates genes involved in starvation response metabolic pathways [ 156 ].…”
Section: Molecular Mechanisms Of the Neuroprotective Effects Of Kbs A...mentioning
confidence: 99%
“…Among the most studied Kbhb residues is histone 3 lysine 9 (H3K9) based on its association with active gene expression when it is acetylated (H3K9ac) at promoter regions 14 . To date, several studies have used H3K9bhb chromatin immunoprecipitation (ChIP) assays to identify BHB-regulated genes in the context of BHB-treatment, starvation, or ketogenic diet 10,[15][16][17][18][19][20] ).…”
Section: Introductionmentioning
confidence: 99%